1999
DOI: 10.1093/ptj/79.1.40
|View full text |Cite
|
Sign up to set email alerts
|

Ketoprofen Tissue Permeation in Swine Following Cathodic Iontophoresis

Abstract: Background and Purpose. Pharmacokinetic assessment of drug tissue permeation following iontophoresis is limited. The depth of ketoprofen tissue permeation following cathodic iontophoresis (4 mA, 40 minutes) and the stereoselectivity of drug delivery were examined in this study.Subjects. Ketoprofen (750 mg) was iontophoresed onto one porcine medial thigh, with passive drug permeation conducted on the other thigh.Methods. Skin, subcutaneous fascia, and muscle biopsies from the drug delivery sites were harvested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…In comparison to the passive application, cathodic iontophoresis enhanced ketoprofen delivery at only the first cm of muscle, but did not enhance ketoprofen delivery in the other tissues analysed. The lack of detectable ketoprofen in the systemic vasculature in the present equine model was similar to our previous ketoprofen results in both man (Panus et al 1996 and swine (Panus et al , 1999. Finally, the absence of measurable ketoprofen in the synovium in the present iontophoretic investigation parallels our previous dexamethsone-phosphate iontophoretic results (Blackford et al 2000).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In comparison to the passive application, cathodic iontophoresis enhanced ketoprofen delivery at only the first cm of muscle, but did not enhance ketoprofen delivery in the other tissues analysed. The lack of detectable ketoprofen in the systemic vasculature in the present equine model was similar to our previous ketoprofen results in both man (Panus et al 1996 and swine (Panus et al , 1999. Finally, the absence of measurable ketoprofen in the synovium in the present iontophoretic investigation parallels our previous dexamethsone-phosphate iontophoretic results (Blackford et al 2000).…”
Section: Discussionsupporting
confidence: 92%
“…The present investigation is the first to examine cathodic iontophoresis of ketoprofen in a compartment this deep in any animal model. Our previous research with cathodic iontophoresis of ketoprofen resulted in measurable concentrations in both man (Panus et al 1996 and swine (Panus et al , 1999. However, in these previous investigations the ketoprofen was measured in more superficial tissues.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In the present investigation, dexamethasone-phosphate and dexamethasone in local venous blood proximal to the application site were utilized as markers of iontophoretic drug delivery to subcutaneous and muscular tissues with access to the vasculature. Our previous research demonstrated that cathodic iontophoresis (4 mA, 40 min, 0.28 mA/cm 2 ) of ketoprofen (300 mg/mL) resulted in transcutaneous permeation of the drug into the subcutaneous fascia and muscle in the pig (Panus et al, 1999). Iontophoresis of ketoprofen under similar conditions onto the human forearm also resulted in approximately 1 mg/mL of the drug in the local venous blood at the termination of iontophoresis (Panus et al, 1996.…”
Section: Discussionmentioning
confidence: 99%
“…Several pharmacokinetic parameters involved with the iontophoresis of ketoprofen, a NSAID, have been documented. Utilizing iontophoretic parameters from clinical practice, cathodic iontophoresis enhanced ketoprofen tissue permeation down to the fascia-superficial muscle interface (Panus et al, 1999). Using the same iontophoretic parameters, ketoprofen iontophoresis at the volar surface of the human wrist resulted in clinically relevant concentrations in the local venous blood when sampled at the ipsilateral antecubital fossa (Panus et al, 1996.…”
Section: Introductionmentioning
confidence: 99%